PENGARUH PEMBELAJARAN BERBASIS DEEP LEARNING TERHADAP HASIL BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA MADRASAH IBTIDAIYAH PADA MATA PELAJARAN MATEMATIKA - Putri Rahayu S (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Low mathematics achievement and critical thinking skills remain significant challenges in elementary education, particularly in Islamic elementary schools (Madrasah Ibtidaiyah). One promising approach to address these issues is deep learning-based instruction, which emphasizes conceptual understanding, active engagement, reflection, and the ability to connect knowledge with real-life contexts. This study aimed to examine the effect of deep learning-based instruction on students’ mathematics achievement and critical thinking skills. The study employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The population consisted of fifth-grade students of Madrasah Ibtidaiyah in Cipondoh District. A total of 60 students were selected through cluster sampling, comprising 30 students in the experimental group and 30 students in the control group. Data were collected through mathematics achievement tests and critical thinking skill tests that had met validity and reliability requirements. Data analysis included normality testing, homogeneity testing, independent sample t-test, and effect size analysis. The findings revealed that the mean posttest score of mathematics achievement in the experimental group (82.73) was higher than that of the control group (74.10). Similarly, the mean posttest score of critical thinking skills in the experimental group (80.20) exceeded that of the control group (71.45). The t-test results indicated significant differences in mathematics achievement (t = 4.62, p = 0.000) and critical thinking skills (t = 4.35, p = 0.000). Furthermore, the effect size values of 1.23 for mathematics achievement and 1.15 for critical thinking skills indicated a strong effect. Therefore, deep learning-based instruction was proven effective in improving students’ mathematics achievement and critical thinking skills in Madrasah Ibtidaiyah.